Hot and Cool Executive Functions in Children with Attention Deficit/Hyperactivity Disorder and Comorbid Oppositional Defiant Disorder - Antonini, Tanya N. (J Int Neuropsychol Soc, 2015)
OBJECTIVE: While neuropsychological deficits in both “hot” and “cool” executive functions (EFs) have been documented among individuals with attention-deficit/hyperactivity disorder (ADHD), these EF deficits are not universal across all individuals with this diagnosis. One potential moderator of executive dysfunction may be the presence of comorbid oppositional defiant disorder (ODD). This study examined the association between “hot” and “cool” EFs and comorbid ODD in children with ADHD. METHOD: Thirty-three children with ADHD and comorbid ODD (ADHD+ODD), 67 with ADHD without ODD (ADHD-ODD), and 30 typically developing controls participated. Children were 7–12 years of age. “Cool” EFs were assessed with a spatial span task and a card sorting test. “Hot” EFs were assessed using a delay discounting task and a gambling task. RESULTS: ADHD-ODD and ADHD+ODD groups performed more poorly on “cool” EF tasks than controls, but did not differ from each other. Further, the number of ADHD symptoms, but not ODD symptoms, was associated with “cool” EF scores. The three groups did not differ on “hot” EF tasks and the number of ADHD or ODD symptoms was unrelated to “hot” EF scores. CONCLUSIONS: In sum, children with ADHD presented with “cool” EF deficits which appear to be unrelated to ODD comorbidity. However, “hot” EF deficits were not present among children with ADHD, irrespective of comorbid ODD status.